2018
DOI: 10.1007/s00705-018-3885-8
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of the complete genome sequence of a potyvirus from passion fruit suggests its taxonomic classification as a member of a new species

Abstract: The complete genomic sequence of a telosma mosaic virus (TeMV) isolate (named PasFru), identified in passion fruit in China, was determined. The entire RNA genome of PasFru comprises 10,049 nucleotides (nt) excluding the poly(A) tail and encodes a polyprotein of 3,173 amino acids (aa), flanked by 5' and 3' untranslated regions (UTR) of 276 and 251 nt, respectively. Compared with the previous TeMV isolate Hanoi from Telosma cordata, the only documented isolate with the entire genome sequence annotated, PasFru h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 6 publications
(6 reference statements)
0
18
0
Order By: Relevance
“…In Potyvirus, P1 is 237 the most divergent protein varying in length and its amino acid sequences (Rohožková & 238 Navrátil 2011), which is considered to be the determinant of potyviruses adapting to a wide 239 range of host species (Valli et al 2007). Yang et al (2018) found molecular differences between 240 TeMV isolate PasFru and Hanoi, particularly in the P1 coding region. A similar observation was 241 also made for two TeMV isolates sequenced in this study -the N-terminal region of P1 242 sequences of Fuzhou and Wuyishan are divergent to Hanoi both in length and amino acid 243 sequences.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…In Potyvirus, P1 is 237 the most divergent protein varying in length and its amino acid sequences (Rohožková & 238 Navrátil 2011), which is considered to be the determinant of potyviruses adapting to a wide 239 range of host species (Valli et al 2007). Yang et al (2018) found molecular differences between 240 TeMV isolate PasFru and Hanoi, particularly in the P1 coding region. A similar observation was 241 also made for two TeMV isolates sequenced in this study -the N-terminal region of P1 242 sequences of Fuzhou and Wuyishan are divergent to Hanoi both in length and amino acid 243 sequences.…”
mentioning
confidence: 88%
“…The disease causes a serious reduction 53 in production and decreases the quality of passion fruit . In 2018, a TeMV 54 isolate named PasFru (accession number MG944249), collected from Haikou Province, was 55 identified and proposed to be a new member of the Potyvirus genus based on analyses of the 56 complete genome sequence (Yang et al 2018). In addition to PasFru, only one complete genome 57 of TeMV isolate (named Hanoi) from Vietnam has been deposited in GenBank (accession 58 number of NC_009742), although TeMV has been identified in many countries.…”
mentioning
confidence: 99%
“…3), suggesting that these isolates share a common ancestral origin. Notably, PasFru was not placed in a new taxon, although it was proposed to be a new member of the Potyvirus species (Yang et al, 2018). Hanoi, isolated from T. cordata in Vietnam, was clustered in an outer branch of the other TeMV isolates collected from P. edulis in China.…”
Section: Phylogenetic Classification Of Temvmentioning
confidence: 99%
“…TeMV was firstly reported to infect Chinese violet (Telosma cordata) in Vietnam (Ha et al, 2008), patchouli (Pogostemon cablin) in Indonesia (Noveriza et al, 2012), then passion fruit in Thailand (Chiemsombat, Prammanee & Pipattanawong, 2014). Recently this virus has also been reported to be present in China (Chen et al, 2018;Xie et al, 2017;Yang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation